2021
DOI: 10.35741/issn.0258-2724.56.5.14
|View full text |Cite
|
Sign up to set email alerts
|

Anomaly-Based Intrusion Detection for a Vehicle Can Bus: A Case for Hyundai Avante Cn7

Abstract: Flooding, spoofing, replay, and fuzzing are common in various types of attacks faced by enterprises and various network systems. In-vehicle network systems are not immune to attacks and threats. Intrusion detection systems using different algorithms are proposed to enhance the security of the in-vehicle network. We use a dataset provided and collected in "Car Hacking: Attack and Defense Challenge" during 2020. This dataset has been realized by the organizers of the challenge for security researchers. With the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…After carrying out model training and validation, we evaluate the performance of the model using standard performance metrics such as accuracy, precision, recall, and F1-score (using Eqs. ( 1)-( 4)) [35,36]. 5, and it shows that, across the three models for the two experimental setups, LSTM achieve the best performance, particularly in experimental setup one, with an accuracy of 98.09%, precision of 98.14%, F1-score of 98.09%, and recall of 98.05%.…”
Section: Resultsmentioning
confidence: 89%
“…After carrying out model training and validation, we evaluate the performance of the model using standard performance metrics such as accuracy, precision, recall, and F1-score (using Eqs. ( 1)-( 4)) [35,36]. 5, and it shows that, across the three models for the two experimental setups, LSTM achieve the best performance, particularly in experimental setup one, with an accuracy of 98.09%, precision of 98.14%, F1-score of 98.09%, and recall of 98.05%.…”
Section: Resultsmentioning
confidence: 89%
“…According to the result provided in Okokpujie et al [20], the authors used the Support Vector Machine (SVM) model and the DeepFNN. After the performance evaluation of both models, the classification report revealed that the Radial basis kernel of SVM provided satisfactory results in terms of Fmeasures in the proportion of 64% and 80% for fuzzing and flooding attacks respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Considering models are not always suitable for all applications, the technique used in this work differs from that of the authors in Lee et al [19], who did not adopt a machine learning approach. On the other hand, in Okokpujie et al [20], DeepFNN and SVM models were used for the classification. However, all features were used as one.…”
Section: Types Of Attacks (A) Fuzzy Attackmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional surveillance systems predominantly comprised analogue cameras connected via coaxial cables. However, with evolving technology, Closed-Circuit Television (CCTV) systems continue to be a staple in maintaining public order and security [2][3][4][5]. In response to cost and performance considerations, a shift towards digital systems has been observed, with current data transmission relying on Internet Protocol (IP) [6,7].…”
Section: Introductionmentioning
confidence: 99%